The Concept of Learning Media in the Perspective of the Qur'an and Al-Hadith - Riza Faishol; Imam Mashuri (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
Learning media has a very important role in the teaching and learning process because the vagueness of the material presented can be helped by presenting the media as an intermediary for delivering messages. This paper discusses the concept of learning media in the perspective of the Qur'an and al-Hadith. The research method used in this study is the literature study method. The data collection technique used in this literature research is the documentation method. Data analysis techniques are content analysis methods. To maintain the conservation of the assessment process and prevent and overcome errors that can occur due to the researcher's lack of knowledge, checks are carried out between libraries and re-reading the library and pay attention to the comments of the supervisor. Learning media is a set of tools (materials) that can convey messages in the teaching and learning process, from the source of the message (teacher) to the recipient of the message (student) to achieve the learning goals that have been set. Learning media in the perspective of the Qur'an and Hadith, can be viewed and classified into audio, visual and audio-visual media.